Strange meson production in Al+Al collisions at 1.9A GeV - Gasik, Piotr; Piasecki, Krzysztof; Herrmann, Norbert; Benabderrahmane, Mohamed Lotfi; Deppner, Ingo Martin; Reischl, Alexander Antonius; Tyminski, Z.; Wisniewski, Krzysztof; Zhang, Y.; Zinyuk, Victoria (Arxiv, 2016)
The production of K$^+$, K$^-$ and $\varphi$(1020) mesons is studied in Al+Al collisions at a beam energy of 1.9A GeV which is close or below the production threshold in NN reactions. Inverse slopes, anisotropy parameters, and total emission yields of K$^{\pm}$ mesons are obtained. A comparison of the ratio of kinetic energy distributions of K$^-$ and K$^+$ mesons to the HSD transport model calculations suggests that the inclusion of the in-medium modifications of kaon properties is necessary to reproduce the ratio. The inverse slope and total yield of $\phi$ mesons are deduced. The contribution to K$^-$ production from $\phi$ meson decays is found to be [17 $\pm$ 3 (stat) $^{+2}_{-7}$ (syst)] %. The results are in line with previous K$^{\pm}$ and $\phi$ data obtained for different colliding systems at similar incident beam energies.
Gesehen am 18.05.2020